Towards realistic simulations of human cough: Effect of droplet emission duration and spread angle. (February 2022) - Li, Mogeng; Chong, Kai Leong; Ng, Chong Shen; Bahl, Prateek; de Silva, Charitha M.; Verzicco, Roberto; Doolan, Con; MacIntyre, C. Raina; Lohse, Detlef
Abstract: Human respiratory events, such as coughing and sneezing, play an important role in the host-to-host airborne transmission of diseases. Thus, there has been a substantial effort in understanding these processes: various analytical or numerical models have been developed to describe them, but their validity has not been fully assessed due to the difficulty of a direct comparison with real human exhalations. In this study, we report a unique comparison between datasets that have both detailed measurements of a real human cough using spirometer and particle tracking velocimetry, and direct numerical simulation at similar conditions. By examining the experimental data, we find that the injection velocity at the mouth is not uni-directional. Instead, the droplets are injected into various directions, with their trajectories forming a cone shape in space. Furthermore, we find that the period of droplet emissions is much shorter than that of the cough: experimental results indicate that the droplets with an initial diameter ≳ 10 μ m are emitted within the first 0.05 s, whereas the cough duration is closer to 1 s. These two features (the spread in the direction of injection velocity and the short duration of droplet emission) are incorporated into our direct numerical simulation, leading to an improved agreement with the experimental measurements. Thus, to have accurate representations of human expulsions in respiratory models, it is imperative to include parametrisation of these two features. Highlights: The injection velocity of a cough at the mouth is not uni-directional. Droplets are emitted only at the very beginning of a cough. Simulation with these two features incorporated agrees better with experiments.